Edukasi Pasar Modal Syariah untuk Menumbuhkan Minat Investasi bagi Mahasiswa UIN Raden Fatah Palembang - Mawardi Mawardi; Lemiyana Lemiyana (Jurnal Pengabdian Pada Masyarakat, 2020)
SHARIA CAPITAL MARKET EDUCATION TO GROW INVESTMENT INTERESTS FOR STUDENTS OF RADEN FATAH ISLAMIC STATE ISLAMIC UNIVERSITY PALEMBANG. In general, the purpose of this community service activity is, Building the attention and interest of students regarding the Capital Market and investing in the Capital Market as well as providing education to students about and investing in the Capital Market so that the need to invest and increase the number of new investors and increase active investors in UIN Raden Fatah Palembang. With this community service activity there is a problem of lack of information literacy about investment and how to invest will increase with the provision of related educational material in the form of training. Meanwhile, because it is related to aspects of intellect and skills, this activity is carried out through education and training. Increased knowledge of information about financial planning can be through stock simulations. The target of this activity is students of the Faculty of Economics and Islamic Business at UIN Raden Fatah. The activity participants are expected to be the main role that can share information and build public awareness in investing.